2003
DOI: 10.1136/ard.62.5.460
|View full text |Cite
|
Sign up to set email alerts
|

Expression of macrophage migration inhibitory factor in diffuse systemic sclerosis

Abstract: Objective: To evaluate whether, in patients with the diffuse form of systemic sclerosis (dSSc), macrophage migration inhibitory factor (MIF) production is dysregulated. Methods: 10 patients with dSSc and 10 healthy controls, matched for age and sex, were studied. MIF expression was evaluated by immunohistochemistry on formalin fixed skin biopsies of patients with dSSc and controls. MIF levels were assayed in the sera and in the supernatants of skin cultured fibroblasts by a colorimetric sandwich enzyme linked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 29 publications
(27 reference statements)
4
35
0
Order By: Relevance
“…Here, we examined concentrations of serum MIF and DDT in SSc and HC, in order to determine their clinical associations in SSc. In line with previous studies,9, 15 we found a significant increase in serum MIF concentrations in SSc patients compared to HC. However, there was no significant difference in serum DDT between SSc and HC.…”
Section: Discussionsupporting
confidence: 93%
“…Here, we examined concentrations of serum MIF and DDT in SSc and HC, in order to determine their clinical associations in SSc. In line with previous studies,9, 15 we found a significant increase in serum MIF concentrations in SSc patients compared to HC. However, there was no significant difference in serum DDT between SSc and HC.…”
Section: Discussionsupporting
confidence: 93%
“…Foote et al examined the associations between serum MIF concentrations and diseaserelated indices of systemic lupus erythematosus (SLE) and corticosteroid use [31]: serum MIF concentrations were positively associated with SLE disease activity and with corticosteroid dose [31]. In view of its multiple functions, MIF may be a critical mediator of inflammation and damage in SLE, and that targeting MIF may offer considerable therapeutic benefits for treating this disease [32].…”
Section: Mif and Autoimmune Skin Diseasesmentioning
confidence: 99%
“…Several cell populations, including T cells (Bacher et al 1996), macrophages/monocytes (Calandra et al 1994), synovial fibroblasts (Leech et al 1999) and endothelial cells (Nishihira et al 1998) express and secrete MIF. Furthermore, MIF is implicated in various inflammatory and immune-mediated diseases, including RA (Leech, Metz et al 1999;Ayoub et al 2008), SLE (Hoi et al 2003;Foote et al 2004), scleroderma (Selvi et al 2003) and inflammatory bowel diseases (de Jong et al 2001). Serum MIF levels are also increased in systemic vasculitis, including WG and AAV (Ohwatari et al 2001;Becker et al 2006).…”
Section: Mifmentioning
confidence: 99%